Exploring the mechanisms linking perceived school climate to negative emotions in adolescents: The mediating roles of social avoidance and distress, and psychological resilience, with physical exercise level as a moderator - Zhen Huang; Weisong Chen; Bo Peng; Haibo Yan (PLoS ONE, 2025)
This study investigates the relationships between perceived school climate (PSC) and negative emotions (NEE) in adolescents, incorporating the mediating roles of social avoidance and distress (SAD) and psychological resilience (PSR) and examining the moderating influence of physical exercise level (PEL). Data were collected from 1,507 students in grades 5–9 across China using stratified random sampling. Demographic analysis revealed significant differences across gender, grade, and family location in PSC, SAD, PSR, NEE, and PEL. Structural equation modeling confirmed that PSC directly reduces NEE and exerts additional indirect effects through SAD and PSR, with a sequential chain mediation pathway accounting for the majority of the total effect. Multi-group analysis demonstrated structural invariance across genders. Moderation analysis indicated that PEL amplifies the protective effects of PSC on NEE, with higher levels of physical exercise strengthening this association. These findings provide comprehensive insights into the interplay of environmental, psychological, and behavioral factors, offering valuable implications for targeted educational and policy interventions.